A Case of Extra-axial Cavernous Angioma Originating from the Oculomotor Nerve - Toshitaka Inui; Hiroyuki Hashimoto; Kenta Fujimoto; Tateo Shimokawara; Mitsuhisa Nishiguchi; Syohei Yokoyama; Koji Omoto; Ryuta Matsuoka; Takahide Yaegaki (Indian Journal of Neurosurgery)
Abstract We report a case of extra-axial cavernous angioma, which originated from the oculomotor nerve and, by hemorrhaging, resulted in oculomotor nerve palsy. Cavernous angioma generally occurs in the brain parenchyma. Therefore, this case is extremely rare. We believe that preoperative sequential magnetic resonance imaging contributed to preoperative diagnosis in this case.